Cough-Induced Spontaneous Rupture of the Kidney Secondary to Anticoagulant Therapy: Wunderlich’s Syndrome - Kamil Fehmi Narter (Journal of Urological Surgery, 2017)
Spontaneous renal or other organ ruptures secondary to anticoagulants have rarely been reported. The clinical features of renal rupture include acute flank/abdominal pain, haematuria, hypotension and shock. It can occur due to increased intraabdominal pressure during coughing. Rupture is most commonly caused by renal tumors such as angiomyolipomas. In the literature, other known causes are long-term haemodialysis, arteriosclerosis or arteritis. Wunderlich’s syndrome is an extremely dangerous complication that may cause death if not treated intensively. If the haemorrhage is self-limiting and the patient is responsive to fluid replacement, the patient can be managed conservatively. Selective angiographic embolization and emergency nephrectomy (partial or total) are the treatment options. In the literature, we found only one case that was presented as spontaneous non-traumatic renal rupture associated with coughing. In our case, total nephrectomy had to be performed, but it was not adequate.